Variabilidade genética e estruturação populacional do Bicudinho-do-brejo-paulista, Formicivora paludicola (aves: Thamnophilidae): uma espécie criticamente ameaçada do estado de São Paulo - Camargo, Crisley de [UNESP] (2014)
Small populations are more susceptible to genetic drift and inbreeding effects which, generally, can be associated to loss of genetic variability. Low levels of genetic diversity can result in severe effects in the individuals, as fertility alterations and capability of adaption to environmental changes. Although these factors can, in turn, increase the risk of extinction, gene flow may balance these effects, maintaining the genetic variability and reducing genetic divergences among populations. Therefore, it is essential to understand intra and inter population genetic data, in order to conserve threatened species. Molecular markers, such as microsatellites and SNPs (Single Nucleotide Polymorphisms), are reliable tools for assessing levels of genetic variability and patterns of gene flow in populations and have been widely used to analyze target species on conservation programs. The São Paulo marsh antwren (Formicivora paludicola) is a small bird restricted to marshes of Atlantic Forest that was recently described in the metropolitan region of São Paulo city. It occurs in 15 isolated localities spread on High Tietê and Paraíba do Sul River basins and, especially due to its habitat destruction, it is already considered as Critically Endangered in São Paulo State. Priorities actions for this species' conservation include genetic studies to establish the monitoring and management of natural populations. Therefore, the present study aimed to evaluate the genetic variability levels and the gene flow patterns of two populations of F. paludicola in order to support future conservation strategies for the species. As so, we analyzed 9 species-specific microsatellite loci and 8 additional heterologous loci, and also 1.227 SNPs loci that were developed by a RAD-seq (Restriction-site Associated DNA sequencing) approach. A total of 44 animals were collected in two marsh areas near Mogi das Cruzes city (MC) (N = 26) and Salesópolis city (SL) ...